ANALISIS KEMAMPUAN PEMECAHAN MASALAH FISIKA SETELAH PENERAPAN MODEL PBL PADA MATERI GELOMBANG BUNYI SISWA KELAS XI SMAN 1 UKUI - Eka Dewi Susanti; Mitri Irianti; Zuhdi Ma’aruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract : One of the problems facing education today is that the ability of students to solve problems when working on questions is still very low. Students still have difficulty solving problems and steps to solve problems given in the form of questions. Students' problem-solving abilities can be trained and improved by carrying out learning activities that invite students to explore, investigate, find problems and solve problems. One of the learning models that can develop these abilities is the Problem Base Learning learning model. This study aims to analyze students' physics problem-solving abilities in Sound Wave material after the application of the problem base learning learning model. The type of research used was the Pre-Experimental Design with the One Shoot Case Study design, namely a group was given treatment in the form of applying the PBL learning model and then the results were observed. The sampling technique used is simple random sampling. The sample in this study were students of SMAN 1 Ukui with class XI MIPA 2 as the experimental class. The research data was collected by giving a test in the form of a posttest which totaled 3 questions which were analyzed descriptively for each indicator. The results of the descriptive analysis showed that students' absorption after learning with the PBL model was already in the good category because most students were able to complete the problem-solving ability test successfully.Keywords: Problem Solving, PBL model, Sound Waves.